2014
DOI: 10.1039/c3fo60470e
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-rich apple (Malus domestica L.) peel extract attenuates arsenic trioxide induced cardiotoxicity in H9c2 cells via its antioxidant activity

Abstract: Evidences suggest that apple peel has a wide range of polyphenols having antioxidant activity and its consumption has been linked with improved health benefits. Arsenic trioxide (ATO) is a very effective drug for the treatment of acute promyelocytic leukemia (APL) but it leads to cardiotoxicity mediated through alterations in various cardiac ion channels and by increasing the intracellular calcium level and reactive oxygen species (ROS). The aim of the present investigation was to study the effect of methanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…In line with previous reports, we showed that ATO treatment can increase ROS production and decrease antioxidant enzyme activity in cardiomyocytes. Therefore, ATO induces oxidative stress in myocardial cells by producing ROS and inhibiting the intrinsic protective antioxidant capacity [29-31]. Consequently, a compound that can decrease ROS overproduction and also prevent cardiomyocyte apoptosis is of great interest to improve the adverse effects of ATO.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous reports, we showed that ATO treatment can increase ROS production and decrease antioxidant enzyme activity in cardiomyocytes. Therefore, ATO induces oxidative stress in myocardial cells by producing ROS and inhibiting the intrinsic protective antioxidant capacity [29-31]. Consequently, a compound that can decrease ROS overproduction and also prevent cardiomyocyte apoptosis is of great interest to improve the adverse effects of ATO.…”
Section: Discussionmentioning
confidence: 99%
“…Various epidemiological, experimental and clinical studies have revealed that natural products in the form of functional foods or nutracuticals play an important role in the prevention and management of cardiac diseases in prophylactic way [10], [11]. High consumption of plant-based foods is associated with a significantly lower risk of coronary artery disease most likely due to the abundance and variety of bioactive compounds present in it [12], [13]. Besides antioxidant activity, natural products have other biological properties like lipid lowering, antihyperglycemic, antihypertensive etc.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of c‐Jun NH 2 ‐terminal kinase and disruption of microtubule are generally involved (Goussetis et al, ). In addition, arsenic trioxide is able to induce apoptosis in many different kinds of cancer or noncancer cells (Chen et al, ; Huang et al, ; Yedjou et al, ; Nakamura et al, ; Selvaraj et al, ; Vineetha et al, ; Mandegary et al, ). It is noteworthy that the complete remission rate of arsenic trioxide treatment is about 85% (29 of 34 patients) in relapsed APL (Kwong et al, ).…”
Section: Introductionmentioning
confidence: 99%